CEA상승을 보이는 폐 유육종증의 1예 - 양미연; 유양선; 고희자; 박세경; 박종숙; 박춘식; 박재성; 백상현; 고은석; 박정미; Yang, Mi-Yean; Ryu, Yang-Seon; et al. (Tuberculosis and respiratory diseases, 2010)
Sarcoidosis is a multi-systemic granulomatous disorder of unknown etiology. The characteristic pathological finding is the presence of non-caseating granulomas. The lungs are primarily affected, however other organs may be involved causing various symptoms and ambiguous laboratory findings can be present. There are a few reported cases of sarcoidosis with elevated tumor markers. We describe a 68-year-old woman presenting with sarcoidosis showing elevated serum carcinoembryonic antigen (CEA). The possibility of cancer arising from serum CEA such as gastrointestinal cancer, breast cancer and lung cancer was excluded. A transbronchial lung biopsy demonstrated a non-caseating granuloma without necrosis. As a result prescribed 30 mg prednisolone daily to the patient and serum CEA was decreased after 1 month of treatment. We report a case of pulmonary sarcoidosis with elevated serum CEA.